Perancangan Turbin BULB Poros Vertikal - Prayudi Prayudi; Fitra Fauzan (JURNAL POWERPLANT, 2015)
PLTMH is power plants, now many in developing good in the village or in isolated areas. One of the type of turbine that potential to PLTMH on the river - river in Indonesia is turbine Bulb. Turbine Bulb is a kind turbine Kaplan who has been developed, turbine was in use on the head with a low efficiency. The "Bulb casing shape" is derived from waterproof upstream that contains a generator inside.turbine Bulb is very suitable for rivers - rivers in Indonesia because the operation turbine was only requires head turbine that low and with water debit. In addition of rivers, is also possible to use of the potential the irrigation drain that has been there. In this final project I'm doing design turbine Bulb with debit (Q) 5m3/s and head 5n.